THU0342 DECLINE IN SUBCLINICAL SYSTEMIC SCLEROSIS PRIMARY HEART INVOLVEMENT ASSOCIATES WITH POOR PROGNOSTIC FACTORS AND ACTIVE INTERSTITIAL LUNG DISEASE. (2nd June 2020) - Dumitru, R. B.; Bissell, L. A.; Erhayiem, B.; Fent, G.; Kidambi, A.; Abignano, G.; Greenwood, J.; Biglands, J.; Del Galdo, F.; Plein, S.; Buch, M. H.
Abstract : Background: Primary systemic sclerosis heart involvement (pSSc-HI) is described in the majority of SSc patients when sensitive methods such as cardiovascular magnetic resonance (CMR) are used 1 . The natural history of these subclinical findings are unknown. Objectives: To evaluate for interval change in subclinical pSSc-HI, the association between change in CMR abnormalities and disease phenotype and whether disease modifying antirheumatic (DMARD) and/or vasodilator treatment influence the CMR course. Methods: SSc patients, fulfilling the 2013 ACR/EULAR criteria, with no cardiovascular (CV) disease, diabetes and no more than 2 CV risk factors had two CMRs performed (V1 & V2; minimum 1 year apart). A 3T CMR with late gadolinium enhancement (LGE), T1 mapping for extracellular volume (ECV of diffuse fibrosis) quantification and stress perfusion was undertaken. Results: 31 SSc patients were evaluated, with median (IQR) follow up (between the 2 CMR scans) of 33 (17, 37) months. Median (IQR) age was 52 (47, 60), 32% had diffuse cutaneous SSc, 52% interstitial lung disease (ILD), 29% Scl70+. 4/31 patients had a non-ischaemic LGE pattern suggesting focal fibrosis at V1, with no change in the pattern, distribution, or median (IQR) LGE scar mass between V1 and V2 [1.88 (1.01, 6.34) vs 1.70 (1.21, 4.18)]. At V2, 2 additional patients showed focal fibrosis, of which one had an episode of clinically diagnosed myocarditis. No significant change in ECV, T1 native, myocardial perfusion reserve (MPR) or left ventricle (LV) volumes and function were noted at V2 compared with V1 (p>0.01). SSc patients with either increase in pre-existing LGE scar mass (n=1) or new fibrosis were all dcSSc, with ILD, 2 Scl70+. A reduction in forced vital capacity and total lung capacity associated with a reduction in LV ejection fraction (LVEF) (rho=0.413, p=0.021; rho-0.335, p=0.07) and MPR (rho=0.543, p=0.007; rho=0.627, p=0.002). Patients receiving DMARD treatment had higher baseline LV end-diastolic volume compared to those with no DMARD treatment [mean (SD) 78 (19) vs 69 (10), p=0.167]. A decrease in LV stroke volume and an increase in T1 native at V1 vs V2 was noted for those on DMARD [mean (SD) 49 (8) vs 46 (8), p =0.023; 1208 (65) vs 1265 (56), p=0.008 respectively] (Figure 1 ). No significant change in CMR measures in those receiving vasodilator or angiotensin-converting-enzyme inhibitor treatment was noted (p>0.01). Conclusion: This first, pilot longitudinal study of CMR-defined subclinical pSSc-HI suggests largely stable appearances with follow-up. Progression of new focal fibrosis and decline in LV function and MPR, where observed, associated with poor prognostic factors of SSc and ILD progression. Consistent with this, individuals on DMARD appeared to show interval decline. Larger longitudinal studies are warranted to confirm these findings and inform on utility of CMR monitoring of subclinical pSSc-HI in poor prognosis SSc. References: [1]Ntusi NA et al, J Cardiovasc Magn Reson. 2014 Disclosure of Interests: Raluca-Bianca Dumitru: None declared, Lesley Anne Bissell: None declared, Bara Erhayiem: None declared, Graham Fent: None declared, Ananth Kidambi: None declared, Giuseppina Abignano: None declared, John Greenwood: None declared, John Biglands: None declared, Francesco Del Galdo: None declared, Sven Plein: None declared, Maya H Buch Grant/research support from: Pfizer, Roche, and UCB, Consultant of: Pfizer; AbbVie; Eli Lilly; Gilead Sciences, Inc.; Merck-Serono; Sandoz; and Sanofi